THREE APPROACHES OF WORD SENTENCE MEANING IN TRANSLATION OF ENGLISH SLANG WORD INTO INDONESIAN IN THE NOVEL “THE ADVENTURE OF OLIVER TWIST” - Ni Putu Wintia Sunny (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2015)
The slang expression means coming to democratic atmosphere in language since the meaning embodied is not absolute. It depends upon who uses it, in which group the users belong to, and in what situation slang word occur. Having knowledge of slang, it means the user is bilingual, or even multilingual. The question emerged is how the user of slang employ slang in their daily communication. Their choice of certain slang replacing the standard may have a certain purposes. Therefore, it is really difficult to translate it in Indonesian. How to transfer the meaning of slang that contains senses about culture, habit, and identity of specific group of people is a complex undertaking. The form of English slang used in the novel "The Adventure of Oliver Twist” by Charles Dickens is generally in the form of primary slang. There were sixteen primary slang words uttered by the character in the novel. However, there was only four secondary slang words found in the novel. So the primary slang more common used by the character in novel. There are three approaches that can be used to find the conceptual meaning of word in the process of translation. There are reference theory, componential analysis, and meaning postulate.